Violence et conflits dans l’armée de la Monarchie Hispanique en Castille : quelques propositions de recherche et de méthodologie - Antonio Jiménez Estrella (Les Cahiers de Framespa)
Army and war are certainly the most important sources of violence of Early Modern History. In this period, there was a significant increase in the size of armies and a multiplication of conflicts between the great European states, with several effects on the civil population. However, in this article about Castile in the sixteenth and seventeenth centuries, we analyze other kinds of violence, that might be called structural, long-term violence, caused by the presence of the army on the territory, and that involved problems such as the recruitment of men for war in times of strong fiscal pressure, desertion, accomodation of soldiers in civil houses, etc. We also study the particular case of the Kingdom of Granada, whose status as border with the North of Africa required the presence of an important permanent military force that caused conflicts. In this case, the situation was still further complicated by the fact that most of those soldiers were living in the main cities of the kingdom, that they were members of the elites and local power networks, and often used military jurisdiction to protect themselves from civil courts. This article shows new methodological approaches and different types of sources for analysis and comparison, in order to provide a most comprehensive and complex view of the structural violence that occurred not only between the military and civilian population but also among members of the army.